2019
DOI: 10.1016/j.ijcard.2019.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Systematic COronary Risk Evaluation - Older Persons (SCORE-OP) in the EPIC-Norfolk prospective population study

Abstract: Background: The Systematic COronary Risk Evaluation -Older Persons (SCORE-OP) algorithm is developed to assess 10-year risk of death due to cardiovascular disease (CVD) in individuals aged ≥65 years. We studied the performance of SCORE-OP in the European Prospective Investigation of Cancer Norfolk (EPIC-Norfolk) prospective population cohort. Methods: 10-year CVD mortality as predicted by SCORE-OP was compared with observed CVD mortality among individuals in the EPIC-Norfolk cohort. Persons aged 65-79 years wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…In our cohort comprised of older persons, we found that SCORE OP yielded higher risk estimates than SCORE (with mathematical correction). The same result was found in the only published external validation of the SCORE OP [24]. While the authors attributed this inconsistency with the previous cross-sectional study [35,36] to a difference in the methods used, we think it may have arisen because of a difference in age composition of the participants.…”
Section: Plos Onesupporting
confidence: 65%
See 4 more Smart Citations
“…In our cohort comprised of older persons, we found that SCORE OP yielded higher risk estimates than SCORE (with mathematical correction). The same result was found in the only published external validation of the SCORE OP [24]. While the authors attributed this inconsistency with the previous cross-sectional study [35,36] to a difference in the methods used, we think it may have arisen because of a difference in age composition of the participants.…”
Section: Plos Onesupporting
confidence: 65%
“…Their results about the transportability of the SCORE OP and SCORE among older persons were divergent compared to ours. In this UK population, the SCORE OP showed "excellent calibration", performing better than the SCORE, despite showing low discrimination ability [24]. Interestingly, in this UK cohort, diabetes prevalence was extremely low, around 3% [24], likely because this information was only self-reported.…”
Section: Plos Onementioning
confidence: 72%
See 3 more Smart Citations